Generation M : Young Muslims Changing the World - Janmohamed, Shelina (London I.B. Tauris & Co. Ltd., 2016)
There is a segment of the world's 1.8 billion Muslims that is more influential than any other, and will shape not just the future of Muslims, but also the world around them. The Arab spring - though in many ways thwarted - has nevertheless raised the prospect of a segment of Islamic societies which has an eye on the future of the Muslim world. Who are they? What drives them? The growing consumer power of Muslims, young Muslims in particular, is a trend that cannot be ignored. This new generation of Muslims are a tech-savvy, self-empowered, youthful group who believe that their identity encompasses both faith and modernity. For these Muslims, their faith affects everything, informing the way they consume, interact, work, and spend their leisure time. Shelina Janmohamed here explores this growing cultural phenomenon, at a time where understanding the mindset of Muslim youths, and what drives them, is critical. Exploring fashion magazines, to social networking and everyday consumer choices, this book shows how these young Muslims are not only adapting to Western consumerism, but reclaiming it as their own. Based on groundbreaking and extensive research undertaken by Ogilvy Noor, the world's first bespoke global Islamic branding practice, Janmohamed provides a unique and timely insight into the lives, and future, of the contemporary, global Muslim population.
Include Illustrations, Glossary, Further Readings and Index.
Keywords: Muslim youth--Attitudes -- Muslim youth--Social conditions